Using Implementation Science to Understand Barriers to Telemedicine Use for Burn Care During a Crisis. - Bettencourt, Amanda P; Davis, Theresa M; Aryal, Subhash; Rhodes, Joseph; Johnston, Mark J; Wegryn, Cindy; Supple, Matthew D; Joe, Victor C; Schulz, John; Vercruysse, Gary (Journal of Burn Care & Research)
During a crisis, hospitals need help to meet the needs of patients with burns. Very few clinicians (1%) of medical doctors and registered nurses and few hospitals (2%) have burn care expertise. Due to these capacity limitations, patients with burns as extensive as 40% TBSA remain outside of burn centers for days to weeks before reaching definitive care. Telemedicine technology (TT) effectively connects a caregiver in any location to an expert burn clinician. However, it remains underused for unknown reasons. Implementation science seeks to uncover the factors affecting the use of innovations like telemedicine to increase uptake. We administered a questionnaire to assess burn center and emergency department clinician perceptions of the feasibility, acceptability, and intention to use TT across a network of 24 hospitals representing 4 of the 6 current American Burn Association disaster response regions. We also collected monthly current TT referral usage rates (# acute burn referrals using TT / # total acute burn referrals). Clinician ratings were generally in the neutral to agreeable (3.04 to 4.01) range for acceptability, feasibility, and intention to use; however, there was no significant relationship between these constructs and the actual use of teleconsultation across the sample. Strong correlations between feasibility and intention to use were observed. However, weaker correlations between ease of use and perceived usefulness suggest that interventions targeting these perceptions are needed to fully realize the potential of teleconsultation in improving the quality of initial and ongoing burn care during a crisis and usual care.